2022
DOI: 10.1017/s1092852922000992
|View full text |Cite
|
Sign up to set email alerts
|

A new era in the diagnosis and treatment of tardive dyskinesia

Abstract: Tardive dyskinesia (TD) is a heterogeneous, hyperkinetic movement disorder induced by dopamine-receptor blocking agents that presents a unique challenge in the treatment of psychosis. Although acceptance of TD as a serious consequence of antipsychotic treatment was resisted initially, subsequent research by many investigators in psychopharmacology contributed to a rich store of knowledge on many aspects of the disorder. While basic neuroscience investigations continue to deepen our understanding of underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 169 publications
0
8
0
1
Order By: Relevance
“…These forms are also called orofacial and limb-truncal TD. For a more detailed description of the clinical manifestations, reference is made here to some of the numerous review articles ( Van Harten and Tenback, 2011 ; Waln and Jankovic, 2013 ; Savitt and Jankovic, 2018 ; Hirjak et al, 2019 ; Caroff, 2022 ). In respiratory TD, the respiratory muscles and diaphragm are dyskinetic ( Yassa and Lal, 1986 ; Rich and Radwany, 1994 ; Kruk et al, 1995 ; Vorre and Lange, 2019 ).…”
Section: Tardive Dyskinesiamentioning
confidence: 99%
See 3 more Smart Citations
“…These forms are also called orofacial and limb-truncal TD. For a more detailed description of the clinical manifestations, reference is made here to some of the numerous review articles ( Van Harten and Tenback, 2011 ; Waln and Jankovic, 2013 ; Savitt and Jankovic, 2018 ; Hirjak et al, 2019 ; Caroff, 2022 ). In respiratory TD, the respiratory muscles and diaphragm are dyskinetic ( Yassa and Lal, 1986 ; Rich and Radwany, 1994 ; Kruk et al, 1995 ; Vorre and Lange, 2019 ).…”
Section: Tardive Dyskinesiamentioning
confidence: 99%
“…It does deserve mention that a large-scale randomized pragmatic study found no significant differences between the classic perphenazine and the second-generation agents studied ( Caroff et al, 2011 ). Some uncertainty exists about having greater susceptibility to motor side effects as a risk factor for getting and having TD ( Kane and Smith, 1982 ; Miller et al, 2005 ; Solmi et al, 2018 ), in part because it may also be related to hereditary pharmacokinetic or other effect-determining factors ( Loonen et al, 2019 ; Caroff, 2022 ). A consistently found risk factor is advanced age ( Miller et al, 2005 ; Carbon et al, 2017 ; O'Brien, 2016 ; Caroff, 2022 ).…”
Section: Tardive Dyskinesiamentioning
confidence: 99%
See 2 more Smart Citations
“…
227Tardive dyskinesia(TD) is a movement disorder that exhibits a range of clinical manifestations arising as side effects of treatment with dopamine receptor-blocking agents, primarily antipsychotic drugs (APDs) [1,2].Consequently,its management overlaps different disciplines, in particular, psychiatry and neurology.In practice, this canresult ina gap in management whereby patients receive only one aspect of what should ideally bemultidisciplinarycare. Psychiatrists will naturally focus on controllingthe patient'schallenging psychotic symptomsand may not be specialized in the evaluation of the abnormal movements that are a core manifestation of TD [3,4].As a result, exposure of neurologists to TD patients may be limited to when the condition has becomesevere.
…”
mentioning
confidence: 99%